An intial-value technique for self-adjoint singularly perturbed two-point boundary value problems - Padmaja, Poosapati; Aparna, Podila; Gorla, Rama Subba Reddy (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we present an initial value technique for solving self-adjoint singularly perturbed linear boundary value problems. The original problem is reduced to its normal form and the reduced problem is converted to first order initial value problems. This replacement is significant from the computational point of view.
Keywords: initial value technique; boundary value problem; singular perturbation problem